A visit from the United Kingdom: sharing session on advancements in pharmacy education & experiential learning / Associate Prof. Dr. Mahmathi Karuppannan - Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On September 6th, our faculty had the privilege of hosting Professor Matthew Boyd from the University of Nottingham (UoN), United Kingdom. Prof. Matthew is the head of the Division of Pharmacy Practice and Policy in the School of Pharmacy, UoN. He is also the school and faculty lead for fitness to practise and the academic lead for experiential learning. SHARING SESSION ON ADVANCEMENTS IN PHARMACY EDUCATION & EXPERIENTIAL LEARNING A Visit from the United Kingdom: Prof. Matt started with an overview of the United Kingdom (UK)'s healthcare system, the National Health Service (NHS). The NHS, founded in 1948, is a publicly funded healthcare system that provides comprehensive, accessible, and cost effective healthcare to all residents of the UK. Prof. Matt emphasised the core principles of the NHS, which include providing healthcare for all citizens based on need, not ability to pay. Prof Matt also shared the current priorities of the NHS. These priorities are dynamic, adapting to the evolving healthcare landscape. They encompass health inequalities improvement, elective recovery, mental health, integrated care, primary care, cancer, and digital transformation.